Implementasi Strategi Digital Marketing pada Segmen B2C untuk Menarik Nasabah - Ahmad, Nawawi; Hidayat, Rahmat (Journal of Business and Economics Research (JBE), 2024)
Every company or business actor has its own way or strategy for running its business in the era of digitalization. The presence of the internet has changed some of the basic rules of marketing in the traditional world to digital marketing. This research aims to determine the implementation of digital marketing strategies in the B2C (Business to Customer) segment in order to attract the interest of novice customers at PT. Pegadaian branch Kp. Weeds. The qualitative method is the method used in this research. This research began with a series of qualitative interviews identifying relationships that required more detailed examination. This interview was conducted by the author directly who came to the Kp Branch. Weeds. The results of this research show that the digital marketing strategy that has been used by PT. Pawnshop Branch Kp. Lalang here uses the following digital marketing concept: Digital Devices, PT. Pegadaian Branch Kp. Lalang uses the Digital Devices concept which is used by Digital Platforms media using the Facebook, Twitter, Instagram and Youtube TikTok media platforms and with the help of the Influencer team from the Kp Branch. Lalang. The advantage of implementing digital marketing is that it makes it easier to carry out marketing activities, makes it easier to get product information from PT. Pegadaian, saves time and effort, for PT. Pegadaian Branch Kp. Digital marketing helps reach customers as a whole, costs less, and increases brand awareness.